Severe pneumonia with empyema due to multiple anaerobic infections: case report and literature review - Yu, Fangyu; Zhang, Xiaojing; Li, Yujiao; Gai, Wei; Zheng, Yafeng; Cai, Xudong (Frontiers in Medicine, 2024)
Background: Cases of severe pneumonia complicated by empyema due to normal anaerobic flora from the oral cavity are infrequent. Diagnosing anaerobic infections through conventional microbiological test (CMT) is often challenging.Case presentation: This study describes the case of a 67-year-old man, bedridden long-term, who developed severe pneumonia with empyema caused by multiple anaerobic bacterial infections. The patient was hospitalized with a five-day history of cough, sputum and fever, accompanied by a twoday history of dyspnea. Despite CMT, the specific etiology remained elusive. However, metagenomic next-generation sequencing (mNGS) identified various anaerobic bacteria in bronchoalveolar lavage fluid (BALF), blood and pleural effusion. The patient was diagnosed with a polymicrobial infection involving multiple anaerobic bacteria. Following treatment with metronidazole and moxifloxacin, the patient's pulmonary symptoms improved.mNGS serves as a valuable adjunctive tool for diagnosting and managing patients whose etiology remains unidentified following CMT.